2013
DOI: 10.1371/journal.pone.0062008
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Novel Contraction-Regulated Myokines Released from Primary Human Skeletal Muscle Cells

Abstract: Proteins secreted by skeletal muscle, so called myokines, have been shown to affect muscle physiology and additionally exert systemic effects on other tissues and organs. Although recent profiling studies have identified numerous myokines, the amount of overlap from these studies indicates that the secretome of skeletal muscle is still incompletely characterized. One limitation of the models used is the lack of contraction, a central characteristic of muscle cells. Here we aimed to characterize the secretome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(167 citation statements)
references
References 105 publications
4
149
3
7
Order By: Relevance
“…BDNF mRNA expression and protein has been detected in human skeletal muscle and C2C12 cells [46], and our group recently reported BDNF in the supernatant fraction of human myotubes [2]. While in patients with type 2 diabetes circulating levels of BDNF are decreased independently of obesity [47], exercise has been demonstrated to increase serum BDNF levels and BDNF mRNA and protein expression in human skeletal muscle [46].…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 94%
See 2 more Smart Citations
“…BDNF mRNA expression and protein has been detected in human skeletal muscle and C2C12 cells [46], and our group recently reported BDNF in the supernatant fraction of human myotubes [2]. While in patients with type 2 diabetes circulating levels of BDNF are decreased independently of obesity [47], exercise has been demonstrated to increase serum BDNF levels and BDNF mRNA and protein expression in human skeletal muscle [46].…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 94%
“…The molecular background of this observation still needs to be determined. IL-15, which is expressed in skeletal muscle and released by myotubes [2,35], potentially plays a role in lipid metabolism. Conflicting results have been reported concerning the regulation of IL-15 expression in skeletal muscle and circulating IL-15 upon exercise.…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the authors went through all references of received articles. Studies included in this meta-analysis had to meet all the following criteria: (1) papers reported the associations between circulating irisin and GDM; (2) casecontrol or cross-sectional investigation for GDM; (3) there should be at least two groups involved in a single study (GDM vs. control group). The flow chart for the identification of the studies is shown in Fig.…”
Section: Meta-analysismentioning
confidence: 99%
“…A constant soluble DPP-IV activity in the plasma suggests that regulation of the activity level is controlled via a long-term mechanism. The mechanisms by which soluble DPP-IV in the plasma is controlled are currently unknown, but possible contributors are the muscle, fat, and T-cells [30][31][32].…”
Section: Plasma Dpp-iv Activity Response To Carbohydratesmentioning
confidence: 99%